2016
DOI: 10.1002/fam.2348
|View full text |Cite
|
Sign up to set email alerts
|

Fire resistance of geopolymer concrete produced from Elazığ ferrochrome slag

Abstract: SUMMARYThis paper presents the effect of elevated temperatures up to 700°C on compressive strength and water absorption of two alkali-activated aluminosilicate composites (one of them is river sand aggregate geopolymer concrete; the other one is crushed sand aggregate geopolymer concrete) and ordinary Portland cement based concretes. To obtain binding geopolymer material, Elazığ ferrochrome slag was ground as fine as cement, and then it was alkali activated with chemical (NaOH and Na 2 SiO 3 ). Geopolymer conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…The colour of the samples turned slightly lighter. The lightening of sample colours has been observed by Turkmen et al [56] and Zhang et al [57] for geopolymers based on slag and metakaolin-fly ash, respectively. It was supposed that the changing in colour is due to the dehydration of moisture and phase transformation at elevated temperature.…”
Section: Kaolin Geopolymer Ceramics (Kgc)mentioning
confidence: 71%
“…The colour of the samples turned slightly lighter. The lightening of sample colours has been observed by Turkmen et al [56] and Zhang et al [57] for geopolymers based on slag and metakaolin-fly ash, respectively. It was supposed that the changing in colour is due to the dehydration of moisture and phase transformation at elevated temperature.…”
Section: Kaolin Geopolymer Ceramics (Kgc)mentioning
confidence: 71%
“…Therefore, the results could provide a strong experimental support for the above hypothesis. Türkmen et al [35] also believed that the beneficial effect of thermal drying was helpful for the increase of compressive strength until 200 °C. Up to 200 °C, the enhancement in compressive strength of FAGCs containing cement also resulted from the following two primary reasons.…”
Section: Resultsmentioning
confidence: 99%
“…The residual compressive strength of NZ-based mortars after their heat treatment is relatively higher than that of the materials on the basis of FA and GGBS. Turkmen et al [38] indicated that a significant decrease in the compressive strength was observed in all of the specimens after heating to 700°C. It was reported that this strength loss is largely attributed to decomposition of calcium hydroxide, which is known to occur between 450 and 500°C [39].…”
Section: Fire Resistancementioning
confidence: 96%